Strategies for facilitating inclusive campuses in higher education : international perspectives on equity and inclusion - Hoffman, Jaimie; Blessinger, Patrick; Makhanya, Mandla (Emerald Publishing Limited, 2019)
Higher education institutions continue to encounter an increasingly complex set of issues regarding equity, diversity and inclusion on university campuses. Many institutions are striving to find creative solutions to eliminate access, participation, and achievement barriers as well as practices that impede retention and graduation rates. This volume provides educators with a global understanding of the successes and challenges associated with facilitating inclusive campuses in higher education amidst the growing diversity of students by providing evidence-based strategies and ideas for implementing equity and inclusion at higher education institutions around the world.By addressing challenges experienced at a cross-cultural level, this book is an invaluable resource for educators and higher education practitioners alike.
Prelims -- Part I: Concepts and principles -- Introduction to strategies for fostering inclusive campuses in higher education -- Part II: Global practices and challenges -- Chapter 1: Removing the rose colored glasses of exclusivity -- Chapter 2: Authentic caring: an Australian experience -- Chapter 3: High-impact inclusive learning organizations: evidence-based strategies in higher education -- Chapter 4: Access4all: policies and practices of social development in higher education -- Chapter 5: Enhancing inclusion, experience, and academic performance: peer-to-peer mentoring for equity group students in an Australian regional university -- Chapter 6: Using virtual communities of practice to coach and mentor faculty to facilitate engaging critical consciousness -- Chapter 7: Afrocentric mentoring models of marginalized individuals in higher education -- Chapter 8: The use of an academic mentorship model to enhance the transition, retention, and success of disadvantaged students in higher education -- Chapter 9: A "critical factor": facilitating the success of students from low socioeconomic status backgrounds at australian regional universities through technology -- Chapter 10: A strategy for enhancing academics' cultural lens: the knowing your students report -- Chapter 11: Innovations and insights for higher education aspiration and outreach programs -- Chapter 12: A collaborative study abroad model: inspiring fiscally underrepresented students -- Chapter 13: Improving bridge programs on American college and university campuses -- Chapter 14: Inclusiveness in the 21st century: Glasgow caledonian university's approach -- Chapter 15: Advocating equity and community through residential learning programs -- Chapter 16: Ensuring equity and inclusion in higher education provision: Ghana's approach -- Chapter 17: Innovative strategies for creating inclusive spaces for hearing-impaired and visually impaired students in an open distance and e-learning (ODEL) environment: a case study of the University of South Africa (UNISA) -- About the authors -- Name Index -- Subject Index.
Includes indexes.
Print version record
Keywords: Inclusive education; Multicultural education; Educational equalization; Education -- Higher; Higher & further education, tertiary education